2022
DOI: 10.3389/fonc.2022.1006278
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel autophagy-related gene model for gastric cancer prognostic prediction

Abstract: Gastric cancer (GC) is a major global health issue and one of the leading causes of tumor-associated mortality worldwide. Autophagy is thought to play a critical role in the development and progression of GC, and this process is controlled by a set of conserved regulators termed autophagy-related genes (ATGs). However, the complex contribution of autophagy to cancers is not completely understood. Accordingly, we aimed to develop a prognostic model based on the specific role of ATGs in GC to improve the predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The occurrence of autophagy is complicated associating with more than 30 autophagy-related genes (ATG). Microtubule-associated protein light chain 3 (LC3), the most commonly used autophagy-related marker, has two subforms, LC3-I and LC3-II, and the conversion of LC3-I into LC3-II is a key step in the formation of autophagosome [34,35]. Autophagy has been regarded to play a dual role in the pathological process, acting as an adaptive response to protect tissue from stress, but excessive stimulation of autophagy can be lethal for the excess elimination of cytoplasmic content [27].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of autophagy is complicated associating with more than 30 autophagy-related genes (ATG). Microtubule-associated protein light chain 3 (LC3), the most commonly used autophagy-related marker, has two subforms, LC3-I and LC3-II, and the conversion of LC3-I into LC3-II is a key step in the formation of autophagosome [34,35]. Autophagy has been regarded to play a dual role in the pathological process, acting as an adaptive response to protect tissue from stress, but excessive stimulation of autophagy can be lethal for the excess elimination of cytoplasmic content [27].…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a newly identified programmed cell death, typically characterized by free iron overload and lethal phospholipid peroxide generation. Increasing evidence has demonstrated that inducing ferroptosis represents a promising therapeutic strategy that preferentially targets iron-rich cancer cells such as HCC [ 67 , 68 ], NSCLC [ 69 ], PDAC [ 70 ], leukemia [ 38 ] and GC [ 71 , 72 ], and provides insights into reversing drug resistance in cancers. The mitochondrial electron transport chain is responsible for ATP production.…”
Section: Discussionmentioning
confidence: 99%